Objective Image Quality Measures of Degradation in Compressed Natural Images and their Comparison with Subjective Assessments - Alison K. Cheeseman; Ilona A. Kowalik-Urbaniak; Edward R. Vrscay (International Conference on Image Analysis and Recognition (ICIAR), 2016)
This paper is concerned with the degradation produced in natural images by JPEG compression. Our study has been basically twofold: (i) To find relationships between the amount of compression-induced degradation in an image and its various statistical properties. The goal is to identify blocks that will exhibit lower/higher rates of degradation as the degree of compression increases. (ii) To compare the above objective characterizations with subjective assessments of observers. The conclusions of our study are rather significant in several aspects. First of all, “bad” blocks, i.e., blocks exhibiting greater degrees of degradation visually, have among the lowest RMSEs of all blocks and among the medium-to-highest structural similarity (SSIM)-based errors. Secondly, the standard deviations of “bad” blocks are among the lowest of all blocks, suggesting a kind of “Weber law for compression,” a consequence of contrast masking. Thirdly, “bad” blocks have medium-to-high high-frequency (HF) fractions as opposed to HF content.